Answer: d
Step-by-step explanation: when you bring 3 into the square root, it becomes isqrt(63). when you apply i, it makes the number sqrt(-63)
pretty sure I did it right this time
Answer:
one solution
Step-by-step explanation:
Answer:
D
Step-by-step explanation:
Given the 2 equations
4x - 5y = 18 → (1)
3x - 2y = 10 → (2)
Multiplying (1) by 3 and (2) by - 4, then adding will eliminate the x- term
12x - 15y = 54 → (3)
- 12x + 8y = - 40 → (4)
Add (3) and (4) term by term to eliminate x, that is
- 7y = 14 ( divide both sides by - 7 )
y = - 2
Substitute y = - 2 into either of the 2 equations and solve for x
Substituting into (1)
4x - 5(- 2) = 18
4x + 10 = 18 ( subtract 10 from both sides )
4x = 8 ( divide both sides by 4 )
x = 2
solution is (2, - 2 ) → D
66 is the anwer I think I'm not for sure I hope this helps and you get it right
Answer:
20
Step-by-step explanation:
8/2 equals 4 and 5 x 4 = 20.